Efficacy of Pharmacological Treatments in Managing Generalized Anxiety Disorder among Adults in Saudi Arabia: A Cross-sectional Analysis - Abdulsalam Mohammed Aleid; Abdulaziz Matar Alharthi; Rana Abdulmohsen Alotaibi; Ahmed Mohammed Alasmari; Sharifah Ahmed Alzabdawi; Imtinan Jafar Asaeed; Sarah Mousa Alshuqayfi; Shuruq Mohammed Alzahuf; Aliyah Matar Alharthi; Mostafa Habeeb Alhodibi (Dr. Sulaiman Al Habib Medical Journal)
Introduction: Generalized anxiety disorder (GAD) is a significant mental health concern characterized by excessive and uncontrollable worry about everyday activities. Despite its prevalence, there is a scarcity of research on pharmacological management strategies for GAD, particularly within the Saudi Arabian context. This study aims to address this gap by identifying and evaluating the most commonly used pharmacological strategies among adults in Saudi Arabia. It will assess the effectiveness of these strategies, examine factors influencing the preference of these strategies, and explore the prevalence and impact of adverse effects associated with them. Methods: This cross-sectional study employed stratified random sampling to select a representative sample of adults aged 18 years and above from various regions of Saudi Arabia. Participants provided data through self-administered questionnaires, which included information on sociodemographic characteristics, GAD symptoms, pharmacological strategies utilized, their effectiveness, and any adverse effects. The study’s analytical approach encompassed statistical methods such as correlation, regression, and Chi-square tests, aiming to uncover relationships and patterns among the collected data, particularly focusing on treatment efficacy and the occurrence of adverse effects. Results: We found a demographic skewing among Saudi patients with GAD, particularly toward young adults aged 18–24 and women. The majority of these patients were diagnosed with GAD and had been experiencing symptoms for less than six months. In addition, there was a notable willingness among them to seek professional help. The most commonly used pharmacological strategy was classified as “Others,” with a high satisfaction rate reported by users. Adverse effects were infrequent, affecting only a minority of patients frequently. Selective serotonin reuptake inhibitors demonstrated the highest mean improvement in GAD symptoms, indicating their effectiveness. Our study also emphasized the importance of considering medication side effects, especially for individuals with a greater tendency to adverse events. Conclusion: This research emphasizes the importance of personalized treatment plans, medication efficacy, and side effect profiles for managing GAD in Saudi Arabia. It also underscores the need for evidence-based treatment guidelines and suggests areas for future research to optimize GAD treatment strategies based on individual patient needs and therapy responses.